Making Chorionic Villus Sampling Painless for Both the Patient and the Physician. (1st February 2014) - Gimovsky, Alexis; Khodak-Gelman, Slava; Larsen, John
Abstract : Currently, in common practice, no pain control is provided to the patient undergoing transvaginal chorionic villus sampling (CVS). Chorionic villus sampling is an invasive procedure involving an 18‐gauge needle stick through the abdomen or passage of a suction catheter through the cervix. Furthermore, CVS is a mechanically difficult procedure for the clinician and requires considerable skill and training. There have been prior studies establishing the efficacy of using a topical anesthetic in similar gynecologic procedures. We share our method of performing CVS, which aids in pain relief for the patient and concurrently aids the practitioner in executing this precise procedure.